Scientific Opinion on the risk of Dickeya dianthicola for the EU territory with identification and evaluation of risk reduction options - EFSA Panel on Plant Health (PLH) (EFSA journal, 2013)
The EFSA Panel on Plant Health conducted a pest risk assessment for Dickeya dianthicola for the EU territory under the scenario of current EU plant health legislation and identified and evaluated risk reduction options. The probability of entry was considered low for carnation cuttings and mother plants because association of D. dianthicola with carnation is rare nowadays. Probability of entry was considered higher for other host plants for planting that are not subject to statutory control. However, this pathogen already occurs in these crops in the EU, and its transfer from them to carnation is unlikely. The probability of establishment is high in the open field but low in protected crops. The probability of spread is moderate in the open field but low in protected crops. Under current phytosanitary measures, but with voluntary certification and sanitation practices in place, consequences for carnation are minimal since no carnation crop losses have been reported in the last 25 years. The risk reduction options with best effectiveness and feasibility are those addressing the sanitary status of the propagation material. However, although the prevalence of D. dianthicola on carnation is low at present, current EU measures appear to have some potential weaknesses, particularly because of lack of details on the testing of mother plants. If the current regulation were to be removed, no major consequences or changes in the potential impact of D. dianthicola are expected provided the current general hygiene practices applied in the European voluntary certification schemes are maintained. If, on the other hand, the current legislation were removed and a voluntary certification scheme was not maintained, contamination of carnation crops by D. dianthicola is expected, with ensuing detrimental effects. Additional risk reduction options to reduce the probability of entry, establishment, spread and impact were identified. Uncertainties on the assessment are discussed.